Relevance of Job Stress, Depression, and Suicidal Ideation in New Fire Officials: Focus on Mediating Effect of Depression - Hur, Mira; Song, Hyeonjeong; Kim, Hana (Fire Science and Engineering, 2020)
This study investigated the mediating effect of depression on the correlation of job stress, depression, and suicidal ideation among 1,331 new fire officials who have worked below three years. For analysis, the Korean Occupational Stress Scale, Patient Health Questionnaire-9, and Suicidal Behaviors Questionnaire-Revised were used. First, we examined the mental health status of new fire officials and analyzed the correlation between job stress, depression, and suicidal ideation. The data were analyzed using the multiple regression analysis method to verify the mediating effect of depression on the correlation between job stress and suicidal ideation. The study found that job stress of new fire officials was positively correlated with depression and suicidal ideation. Depression has a positive correlation with suicidal ideation. When the mediating effect of depression was considered, depression was a partial mediator variable between job stress and suicidal ideation. These results suggest that more efficient and timely treatment in a preventive way will help new fire officials reduce job stress and depression. Moreover, it will be more effective to establish a counterplan for suicide prevention for fire officials.